Effect of eccentric overload training on change of direction speed performance: A systematic review and meta-analysis - Liu, R.; Liu, J.; Vitosky Clarke, C.; An, R. (Journal of Sports Sciences, 2020)
This study systematically reviewed and quantified evidence regarding the effectiveness of eccentric overload training (EOT) on change-of-direction speed (CODS) performance. A keyword search was performed in 30 April 2020 in eight electronic bibliographic databases: SPORTDiscus, PubMed, Web of Science, Academic Search Complete, Cochrane Library, Scopus, CINAHL and Google Scholar. A meta-analysis was conducted to estimate the pooled effect size of EOT interventions on CODS performance compared to the control group. Study heterogeneity was assessed by the I 2 index. Publication bias was assessed by the Begg`s and Egger`s tests. Eleven studies, including nine randomized controlled trials, one randomized crossover trial, and one non-randomized controlled trial met the eligibility criteria and were included in the review. Time of overall change-of-direction task completion among the EOT group was 1.35 standard deviations (95% confidence interval [CI] = 0.18, 2.52) shorter than that in the control group. In conclusion, EOT was found effective in improving CODS performance compared to the control group. Future studies should adopt a randomized experimental design, recruit large and representative samples from professional team sports, and examine the effect of EOT on various measures of CODS performance among population subgroups.